P107 Developing A Customised Web-Based Data Extraction Tool Using An Existing Customer Relationship Service: Thinking Outside The Box. (15th August 2013) - Nagler, E; Liébaut, V; Haller, M; van der Veer, S; Bolignano, D; Nistor, I; Van Biesen, W
Abstract : Background: Standardised duplicate data extraction and tabulation can be challenging for organisations that develop multiple guidelines involving multiple and remote systematic review teams simultaneously. Objectives: To develop a web-based tool for facilitating duplicate data extraction and efficient discrepancy resolution. Methods: Based on previous experiences with word-processing and spreadsheet tools, European Renal Best Practice listed their system requirements and collaborated with a consultancy company to identify appropriate customisable software. Results: We wanted the system to: be web-based, guide reviewers through a standardised data extraction form, be easy-to-use and manage, allow enough flexibility to accommodate different guideline topics, be free-of-charge and easily accessible from different locations without the need for downloading software. We identified a customer relationship management service, Salesforce, that allowed us to build a data extraction module using their backbone structure. It incorporates centralised management of multiple systematic reviews simultaneously, batch allocation of studies to individual reviewers, guided customised point-and-click data extraction, generation of tables to assist discrepancy resolution with easy export to a cvs-file extension format. Discussion: This project represents a continuous effort to facilitate efficient and high-quality systematic reviewing with participation of our guideline development groups throughout the systematic reviewing process. A first version of the system is currently being evaluated. Implications for Guideline Developers/Users: Customising existing software for guideline development purposes might be an attractive and inexpensive alternative to developing new tools for data extraction when full participation of the guideline development group in the systematic review process is desired.